Apakah stakeholder pressure dan firm size mampu meningkatkan kualitas pelaporan terpadu dengan kinerja perusahaan sebagai variabel moderasi - Afifah Nidaul Hukama; Khomsiyah Khomsiyah (AKURASI: Jurnal Riset Akuntansi dan Keuangan, 2024)
This study analyzed the influence of stakeholder pressure and company size on integrated reporting and the role of corporate performance as a moderating variable on the influence of stakeholder pressure on integrated reporting. Data for this study were obtained from 36 companies that have published integrated reports listed on the Indonesia Stock Exchange for 2021 to 2023, with 108 observations and hypotheses tested using panel regression analysis with the Eviews 13 program. Content elements of the framework published by the International Integrated Reporting Council were used to measure the quality of integrated reporting in the study. The results revealed that stakeholder pressure had no effect on integrated reporting, Firm Size had a significant influence on integrated reporting, and company performance could not moderate the influence of stakeholder pressure on integrated reporting. Public interest statementsThe managerial implication is that Management needs to pay attention to stakeholder pressure to improve transparency and accountability in integrated reporting. Management must ensure that the reporting is comprehensive, accurate, and relevant, covering financial and non-financial performance aspects. Companies with good performance may be better able to meet stakeholder expectations, and conversely, increasing pressure can encourage companies to improve their performance